A CORRELATION BETWEEN GRATITUDE AND RESILIENCE IN ADOLESCENT ORPHANAGES IN SURAKARTA CITY - yusvi, nabila; Saniatuzzulfa, Rahmah; Kirana Anggarani, Fadjri (Jurnal Studia Insania, 2024)
Adolescents in orphanages are prone to psychological difficulties, making resilience an essential capacity. Gratitude is considered an internal factor that supports resilience. This study aimed to examine the correlation between gratitude and resilience among orphanage adolescents in Surakarta City. Using a quantitative approach and total sampling technique, 81 participants were involved. Two adaptation scales were applied: the Connor Davidson Resilience Scale (CD-RISC 25; 24 items, α=0.940) and the Gratitude Resentment Appreciation Test-Short Form (GRAT-SF; 10 items, α=0.851). Data analysis employed simple linear regression, which revealed a significant positive correlation between gratitude and resilience, with F calc > F table (16.299 > 3.962), correlation coefficient (R) = 0.414, and p < 0.001. Gratitude contributed 17.1% to resilience formation. These findings confirm the hypothesis that gratitude positively influences resilience, suggesting that cultivating gratitude can strengthen psychological adaptability in orphanage adolescents facing life challenges.